México beyond 1968 : revolutionaries, radicals, and repression during the global sixties and subversive seventies - Pensado, Jaime M., 1972-; Ochoa, Enrique (The University of Arizona Press, 2018)
"This book offers a critical look at Mexican activism that expands our understanding of social movements during the Global 1960s."--Provided by publisher.